Analysis of Carrying Capacity of Agricultural Land to Ensure Food Security in the Kei Besar Islands, Southeast Maluku Regency - Pieter J. Kunu (Faculty of Agriculture, Pattimura University, 2020)
Study on assessment carrying capacity of food, especially rice to ensure food security was conducted in the Kei Besar Islands, Southeast Maluku Regency. The results showed that district of Kei Besar has ability to food self-sufficient and to provide a proper life for its community in Northwest and Southwest Kei Besar. While, district of South Kei Besar is able to be self-sufficiency in food but has not able to provide a better life for its communities. On the other hand, district of Northeast Kei Besar is classified as an incapable area to food self-sufficient because the existing population is greater than the availability of rice to food self-sufficiently, namely 2000 people. This shows that there is no balance between the population, demand and the availability of rice in district of Northeast Kei Besar during the year. This means that this area is threatened with food insecurity. By considering the population in this district which is still high above the optimal food self-sufficiently, the following policies are recommended: (1) expansion of upland rice farming on suitable land, (2) migration of population to other less-populated districts; (3) sharing of rice food products from surplus areas to deficit areas and or (4) equitable development to divide population concentrations in these areas.